The effects of race, gender, and alcohol cues on anger perception in crowds - Elizabeth Summerell; Liberty Shuttleworth; Carmen Lin; Thomas F. Denson (Australian Journal of Psychology)
Objective Anger in crowds can be dangerous and lead to violence. Accurately assessing anger in crowds can be difficult, and people tend to overestimate the average intensity of a crowd’s anger relative to an individual’s anger (i.e. the crowd emotion amplification effect).Method Across three experiments, we investigated the emotion amplification effect in crowds (versus individuals) displaying angry facial expressions. We also investigated the influence of gender, race, and alcohol cues as influences on this effect.Results In two of the three experiments, we replicated the emotion amplification effect and found an interaction with race. Participants overestimated anger in White crowds more so than anger in Black crowds, but overestimated anger to a greater extent for Black individuals more than White individuals. There was also a main effect such that participants overestimated anger for men relative to women in both individuals and crowds and in both races.Conclusions These findings highlight the bias to overestimate anger in White crowds, men, and Black individuals. These findings may affect policies around policing and crowd control.